A non-cooperative non-zero-sum game-based dependability assessment of heterogeneous WSNs with malware diffusion. (1st August 2017) - Shen, Shigen; Ma, Haiping; Fan, En; Hu, Keli; Yu, Shui; Liu, Jianhua; Cao, Qiying
Abstract: We consider Heterogeneous Wireless Sensor Networks (HWSNs) with malware diffusion and find a solution to assess their dependability in order to guarantee dependable operations on sending sensed data from sensor nodes (SNs) to a sink node. To this end, we regard an infection as a state transition of a Markov chain and propose a heterogeneous discrete-time Susceptible-Infected-Susceptible (SIS) model to disclose the diffusion process by combining the SNs' heterogeneity with the malware's spread probability, which is foreseen by a developed non-cooperative non-zero-sum game. We further present reliability and availability measures for a susceptible SN from the perspective of reliability theory, from which we deduce and obtain metrics of reliability and availability assessment of HWSNs with star and cluster topologies. We therefore set up a dependability assessment mechanism for HWSNs with malware diffusion. Experiments illustrate the influence of the parameters on malware's selection of the optimal spread probability and the mean time to infection of a susceptible SN. We also validate the effectiveness of the proposed mechanism. Our results can be applied to set up theoretical bases for governing the employment of reliable techniques.